Geist der Pharaonenzeit - Hornung, Erik 1933-2022 (Zürich [u.a.] Artemis-Verl., 1990)
Literaturverz. S. 214 - 218
Includes bibliographical references (p. 214-[218]) and index
Archivierung prüfen
Keywords: Ägypten <Altertum> ; Geistesgeschichte; Philosophy, Egyptian